2022
DOI: 10.3390/cancers14071843
|View full text |Cite
|
Sign up to set email alerts
|

RBM24 in the Post-Transcriptional Regulation of Cancer Progression: Anti-Tumor or Pro-Tumor Activity?

Abstract: RNA-binding proteins are critical post-transcriptional regulators of gene expression. They are implicated in a wide range of physiological and pathological processes by modulating nearly every aspect of RNA metabolisms. Alterations in their expression and function disrupt tissue homeostasis and lead to the occurrence of various cancers. RBM24 is a highly conserved protein that binds to a large spectrum of target mRNAs and regulates many post-transcriptional events ranging from pre-mRNA splicing to mRNA stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 83 publications
(147 reference statements)
0
3
0
Order By: Relevance
“…Though our results suggest RBM24 as an anti-SARS-CoV-2 target, the detail mechanism of RBM24 in virus replication needs more deep investigation. RBM24 was supposed to be a potential therapeutic target for cancer treatment ( Shi, 2022 ), And different efforts such as small molecule inhibitors, siRNA, peptides and CRISPR-based therapies had been made to target RBP functions for cancer therapy ( Mehta et al, 2022 ). However, how to deliver the drugs to specific tissues with minimal cytotoxicity to normal cells is the main question, which is the same for the antivirus purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Though our results suggest RBM24 as an anti-SARS-CoV-2 target, the detail mechanism of RBM24 in virus replication needs more deep investigation. RBM24 was supposed to be a potential therapeutic target for cancer treatment ( Shi, 2022 ), And different efforts such as small molecule inhibitors, siRNA, peptides and CRISPR-based therapies had been made to target RBP functions for cancer therapy ( Mehta et al, 2022 ). However, how to deliver the drugs to specific tissues with minimal cytotoxicity to normal cells is the main question, which is the same for the antivirus purpose.…”
Section: Discussionmentioning
confidence: 99%
“…RBM24 belongs to the family of RNA-binding proteins and can regulate a number of target gene expression through post-transcriptional mechanisms such as pre-mRNA splicing, mRNA stability alteration, polyadenylation, and translation. 13,14 Lu et al 15 reported that RBM24 promotes cardiac myofibrillogenesis by modulating ACTN2 mRNA alternative splicing. In addition to regulation of cell differentiation, 14,15 RBM24 also affects tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…RBPs play a key role in regulating various RNA processes through both temporal and spatial regulation of expression in membranes or phase-separated subcellular compartments of dynamic shuttling, interactions with specific protein partners and RNA targets, and control of all metabolic processes of RNA. This includes splicing, cleavage and polyadenylation as well as translocation, translation and degradation of coding RNAs, non-coding RNAs and microRNAs (3)(4)(5)(6)(7). Recent studies have shown that RBPs not only play important roles in normal cells, but also become major players in cancer development and proliferation (8,9).…”
Section: Introductionmentioning
confidence: 99%